A Systematic Review of Lactation Counseling for Exclusive Breastfeeding - Mardhika, Amellia; Sulistyono, Agus; Sulpat, Emuliana; Harianto, Susilo (International Journal of Psychosocial Rehabilitation, 2020)
There is a need to listen to and accept the mother’s opinion without judgment and helping mothers to make the best choice based on relevant information and advice given by a lactation counselor. This systematic review illustrates the role of lactation counselors, which involves informing pregnant women and new mothers about the benefits and management of breastfeeding. Our main goal was to determine whether breastfeeding education during pregnancy and postnatally can make mothers provide exclusive breastfeeding. A systematic review of the literature concerning breastfeeding counseling and lactation counselors for breastfeeding mothers was undertaken. Electronic databases were searched, including Proquest, Science Direct, Sage, Pubmed, Oxford Academic and Cochrane Library. Databases were searched for articles featuring the terms “mother”, “mothers”, “breastfeeding counseling”, “lactation counselor”, “breastfeeding counselor”, “exclusive breastfeeding", “rct”, “randomized control trial”, “randomized controlled trial” for peer-reviewed manuscripts published between 1 January 2010 to 31 March 2020; 81 manuscripts were obtained. We included all English studies relevant to the topic. The design study used randomized control trial (RCT). All studies found relating to breastfeeding counseling in breastfeeding mothers were included. Eligible studies were those whose title or abstract specifically indicated the inclusion of breastfeeding counseling and they were analyzed using prisma (5 manuscripts). The results of all studies confirm that the effects of breastfeeding counseling programs are significant. The conclusions of the findings of this review encourage efforts for further research on maternal readiness in breastfeeding, and whether lactation counselors are required or breastfeeding health promotion by health workers